VALIDITAS DAN RELIABILITAS PENGUKURAN KELUARGA SEJAHTERA* - Faturochman Faturochman; Agus Dwiyanto (Populasi, 1998)
This article critically examines the family welfare data collected by the National Family Planning Board (BKKBN). Comparing the BKKBN's data with the UGM's data, the article demonstrates significant differences in family distribution, in most of the family welfare indicators. As a result, the categorization of families into family welfare stages between BKKBN's data and UGM's data differs considerably. This raises some issues on the reliability and validity of BKKBN's family welfare registration data. The article also discloses weaknesses embeded in the instrument and data collection processes which may hurt the reliability and validity of the BKKBN's data. Thus, the improvement of the instrument as well as the process of collecting data is absolutely necessary if the BKKBN is to more effectively implement its family welfare programs.